The performance of phosphate solubilizing bacteria (PSB) on growth, phenolic, and flavonoid content of Orthosiphon stamineus (misai kucing) in the presence of different rates of organic fertilizer - Mesenan, Nur Farahain (2016)
Orthosiphon stamineus is the herbal plant that is listed as a high-value product for commercialization, especially in terms of its health benefits. In herbs cultivation, meet the fertilizer application is important at the early stages of planting to achieve its maximum growth. However, now we are facing a serious problem on the lack of P element availability in soils which can cause stunted growth to the plant. In order to overcome this problem, application of organic fertilizer is highly recommended because it can supply nutrients needed by plants. Besides, the uses of phosphate solubilizing bacteria (PSB) that acts as a biofertilizer together with organic fertilizer will help to exchange insoluble phosphorus to the available form for plant uptake. The objective of this study is to determine the effect of phosphate solubilizing bacteria (PSB), the different rates of organic fertilizer and the combination of PSB and organic fertilizer on the growth of O. stamineus. In this experiment, there are six treatments were applied which is control, single used of phosphate solubilizing bacteria (PSB), 56.88g of organic fertilizer, 28.44g of organic fertilizer, the combination of 56.88g of organic fertilizer and PSB, and the combination of 28.44g of organic fertilizer and PSB with five replications for each treatment. These 30 experimental units were arranged in a Complete Randomized Design (CRD) experiment at the Agrobiotechnology Laboratory, Faculty of Agriculture, UPM. Data collection was taken once every 2 weeks after fertilizer application and bacteria inoculation for parameters plant height (cm), number of branches, and chlorophyll content (SPAD unit) and next, the data that was collected at 11th week are fresh and dry weight of roots, leaves, and stems (g), length of roots (cm), total phenolic content (mg GA/ g dry weight) and total flavonoid content (mg RU/ g dry weight). The result obtained show that both of the combined application had a significant effect on all of the parameters except, chlorophyll content parameter.